Motivações para transição de carreira na área de tecnologia da informação: uma abordagem Delphi - Assis, Mariela C. S. Fontenelle Sily de (2016)
Considering the great demand of organizations for information technology (IT) personnel properly trained to meet the needs of the business, it is relevant for companies to be able to hire, retain and motivate their teams for the proper performance of their roles. Companies, in general, have faced difficulty in this regard, since there is a shortage of IT professionals with adequate profile and qualification. It has also been observed an issue namely ‘turnaway’, situation in which IT professionals make career transition to another functional area. Then, the main target of this work is to identify, through a Delphi study, the main motivations that lead IT professionals to migrate to other areas. Besides, this research also sought to obtain a rank by relevance of the antecedents of the career transition to other functional areas, and to compare the results with that presented in previous studies on this subject. Thus, the Delphi group was formed by 35 IT experts, with relevant experience in the field. The results accrued from this research unveil that the need for professional growth, the need to acquire further experiences and skills to remain attractive to employers, the area of activity in IT, prior and conscious development for career transition and exhaustion with work in the IT area are factors that have relevant impact on turnaway intent. On the other hand, low identification with the IT profession, age and gender are factors that have a low impact on turnaway intention.